Bioprospeksi Ekstrak Etanol Batang Serai Dapur Cymbopogon citratus (DC.) Stapf. sebagai Antibakteri Staphylococcus aureus ATCC : 25923 - Reza Anindita; Anna Affifah Ramadhena; Melania Perwitasari; Dede Dwi Nathalia; Maya Uzia Beandrade; Intan Kurnia Putri (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Bioprospection of medicinal plants does not only require empirical information, but also requires scientific evidence information. One of the potential medicinal plants that require scientific evidence regarding the ability of antibacterial activity is lemon grass (Cymbopogon citratus). The purpose of this study was to determine the effectiveness of lemongrass in inhibiting the growth of Staphylococcus aureus bacteria. The design of this study was an experiment using ethanol extract samples of lemon grass stems and bacteria S. aureus ATCC : 25923. The research procedures included: determination, preparation, extraction, evaporation, and phytochemical screening of lemon grass stem powder taken from the Pasir Angin area, Bogor, West Java. Treatments in this study included: ethanol extract of lemon grass stems with concentrations of 10%, 20%, 30%, 40%, 50%, 30µg chloramphenicol as positive control, and sterile distilled water as a negative control. All treatments were given 30µL on MHA media containing S. aureus culture. Data analysis in this study was carried out with a quantitative descriptive test. The results showed that the yield percentage of the viscous extract was 18.59% with positive phytochemical screening for alkaloids, tannins, saponins, flavonoids, and terpenoids. The antibacterial test results of the ethanol extract of lemon grass stem 10%, 20%, 30%, 40%, and 50% against S. aureus were able to produce inhibition zone diameters of 1 mm, 1.25 mm, 2 mm, and 2.41 mm, and 3 mm with sensitivity response category resistant. The conclusion in this study was that the administration of ethanol extract of lemon grass stems with 10%, 20%, 30%, 40%, and 50% was not effective in inhibiting the growth of S. aureus so that the lemon grass stems were taken from the Pasir Angin area, Bogor, West Java not recommended as a candidate raw material for pharmaceutical formulations.